O Princípio de Equivalência - Acevedo, O.a.; Morais, E.m. De; Pimentel, B.m. (Sociedade Brasileira de Física, 2019)
Abstract We review the conceptual basis on the Equivalence Principle, elucidating its crucial role in the formulation of gravitational theories. We analyze the direct consequences of the principle by reinterpreting in a relativistically coherent manner the way it should be considered in the derivation of gravitational redshift by using the relativistic Doppler effect. Einstein missed out this point. The most important experiments already carried out in the search for violations of the equivalence between gravitational mass and inertial mass are reviewed, their operational principles and results are analyzed.

Resumo Revisamos a base conceitual sobre o Princípio de Equivalência, elucidando seu papel crucial na formulação das teorias gravitacionais. Analisamos as consequências diretas do princípio, reinterpretando de modo relativisticamente coerente a forma como deve ser considerado na dedução do redshift gravitacional via utilização do efeito Doppler relativístico, ponto que foi negligenciado por Einstein. Os experimentos mais importantes já realizados a procura por violações da equivalência entre massa gravitacional e massa inercial são comentados, analisando seus princípios de funcionamento e os resultados obtidos.
The Equivalence Principle
Keywords: relativity; gravitation; equivalence principle; doppler effect; free fall; relatividade; gravitação; princípio de equivalência; efeito doppler; queda livre